Complex Treatment in Severe Forms of Acute Paraprocitis (Clinical Case) (Eurasian Scientific Herald, 2023)
Acute Para proctitis is observed in 5-58% cases in a severe form (isheorectal, pelviorectal, retrorectal) (Sheligin Y.A. 2015, Musin A.I. 2017). In severe forms, the wound is cleared of purulent-necrotic tissue and regeneration is slow, and general intoxication is observed. Various means and methods are successfully used after opening the OP to reduce the time of wound cleaning and improve regenerative processes in it. This includes medicinal preparations based on proteolytic enzymes, chemical antiseptics, ointments and polyethylene glycols.